ANTIDIABETIC ACTIVITY OF NANOPARTICLES CONTAINING JAVANESE TURMERIC RHIZOME EXTRACT: THE STRATEGY TO CHANGE PARTICLE SIZE - RAHMAT, DENI; FARIDA, YUNAHARA; BRYLIANTO, AVILLA TAN; SUMARNY, ROS; KUMALA, SHIRLY (International Journal of Applied Pharmaceutics, 2020)
Objective: The aim of this study was to investigate the antidiabetic activity of Javanese turmeric rhizome extract and its nanoparticles. Javanese turmeric rhizome contains curcumin, flavonoid, and xanthorrhizol that show the antidiabetic activity. The plant extracts entrapped within the nanoparticles have been reported to increase the active compound bioavailability. Thereby, the nanoparticles can improve the biological activity of active compounds. Methods: The rhizome was extracted by kinetic maceration using 96% (v/v) ethanol, whereas the nanoparticles were prepared by the ionic gelation method with different formulations to obtain two types of nanoparticles (F1 and F2). The resulting nanoparticles were evaluated for their particle size, zeta potential, and morphology. The antidiabetic study was performed in a model of alloxan-induced diabetic mice. The mice were divided into five groups, namely normal, negative, positive, extract (dose of 400 mg/kg) and nanoparticles group (dose of 400 mg/kg). Afterward, the blood glucose levels were observed within 24 d using a glucometer. Results: The nanoparticles F1 displayed particle size of 157.8±18.0 nm with a polydispersity index of 0.488 and zeta potential of+51.4±4.56 mV. Spray drying process of the suspension of nanoparticles F1 produced a fine yellow powder. In contrast, nanoparticles F2 assembled with a different solvent system gave rise to a smaller particles size (90±20.8 nm) but could not be dried. Hence, the nanoparticles F1 were further studied for the antidiabetic study. The results showed that the nanoparticles; F1 rendered a better antidiabetic activity compared to the extracts. Percentage of decrease in blood glucose levels of the extract and the nanoparticles were 39.62 and 47.52%, respectively. Conclusion: The type of solvent system of the extract could interfere with the resulting particle size of the nanoparticles. The nanoparticles could be promising carriers for the extract to improve the antidiabetic activity.